E-LAPD BASED ON PROBLEM BASED LEARNING TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Ajeng Pramesti, Siti Andini; Yonata, Bertha (Universitas Labuhanbatu, 2025)
Purpose – Development of E-LAPD based on Problem Based Learning to improve students' critical thinking skills on reaction rate material in class XI SMA which is said to be valid, practical, and effective.Methodology – This research is a type of quantitative research with the ADDIE research development model. Data were collected from validation data, student questionnaire sheets, observation sheets, and pretest and posttest question sheets. Then the validation data was analyzed with a Likert scale to test validity, student questionnaire sheets and observation sheets to test practicality, and pretest and posttest question sheets were analyzed using N-Gain to test effectiveness.Findings – The results of the research in the form of E-LAPD based on problem-based learning to improve students' critical thinking skills on reaction rate material in class XI SMA are feasible to use because they meet the valid criteria with an average score of content and construct validation of 4 with a good category. The developed E-LAPD is declared practical in terms of the results of student response questionnaires and observation sheets with a percentage of 97.81%. The E-LAPD developed can be declared effective in training students' critical thinking skills based on the analysis of the N-Gain test results with a result of 0.90 in the high category, so it can be said that there is an increase in scores between before and after the use of E-LAPD.Contribution – Innovation in the development of learning media, namely electronic student activity sheets based on problem-based learning to improve students' critical thinking skills in class XI high school reaction rate material.